Lahirnya Negara Islam Sekuler Turki dan Ide Pembaharuan Mustafa Kemal Attaturk - Nursalam, Nursalam; Yunus, Abd Rahim; Susmihara, Susmihara (AHKAM, 2024)
This article discusses the History of the Islamic State of Turkey and the Reform Ideas of Mustafa Kemal Atatürk. The birth of a modern state is derived from modernity ideas. The interaction between nations contributes to the transmission of ideas about the modern state. Similarly, in Turkey, the idea of the modern state in Europe was transmitted through Mustafa Kemal. As a figure who underwent military education in France, specifically at Picardie Manuvers, he had the opportunity to absorb reform ideas, leading him to transform Turkey into a modern state. Mustafa Kemal saw that the Ottoman Turkish government was not an ideal type of modern governance. The Sultan had absolute power and was not constrained by laws. There was no parliament to control the Sultan's authority. Additionally, the Sultan was powerless against Western influence in bilateral relations, as the West gradually dominated the Ottoman Turkish territory. Subsequently, Mustafa Kemal established an anti-government movement through his organization, Vatan, and boldly resisted the West, successfully reclaiming Turkey's territory from the Allies. Mustafa became renowned among the people and was considered a hero, receiving support and sympathy from the Turkish population.